Complicaciones en madres adolescentes primigestas con infección de vías urinarias en el Hospital San Vicente de Paul, durante el periodo junio-diciembre del 2015. - Vera Rentería, Patricio Andrés (2016)
In order to contribute information to improve the quality of life in a sector of the female population and corresponding to the primigestas teenage mothers, establishing the impact has infections of the urinary tract during their pregnancy and its consequences for being that develops in the womb, and, in turn, allow to draw some guidelines for prevention and treatment. The research work has been done, to determine the complications in primiparous adolescent mothers with urinary tract infection, identify the trimester in which it occurs more often this disease and analyze the complications that show the patients admitted to the San Vicente Hospital Paul, Pasaje city. This study used a retrospective, descriptive, cross-sectional, with the tools necessary for the collection of data and information. During the investigation time and as conclusions we have found (during the investigation period), 215 cases more patients were identified, between 18 and 19 years (40.93%), urinary tract infection, occurred more frequently in the second quarter (49.30%) and third quarter (44.19%) respectively, and of these the most significant pyelonephritis in 54.42%. The gynecological obstetric complications presented were multiple highlighting, the higher percentage of preterm labor at 43.72%, followed by premature rupture of membranes (18.14%), threatened abortion (7.44%), abortion (1.86%).